Beyond Reception: A Critical Reassessment of Snouck Hurgronje and the Formation of Islamic Legal Historiography in the Nusantara Archipelago (14th–16th Centuries) - Sariat Arifia; Yusup Hidayat; Bambang Arif Wibowo (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
The Receptie Theory formulated by Christiaan Snouck Hurgronje has long occupied a central position in the study of Islamic law in the Nusantara, often treated as an objective explanatory framework for the relationship between Islamic law and customary law. However, this dominance has generated a historiographical problem by obscuring the pre-colonial legal realities of the region. This study critically reassesses the Receptie Theory by situating it within the broader context of colonial knowledge production and legal governance, arguing that it functioned not merely as an academic proposition but as an epistemic instrument of colonial power aimed at subordinating Islamic law. Methodologically, the research employs an interdisciplinary approach that integrates Critical Legal Studies, Postcolonial Theory, and Indo-Archaeo-Islamology. The analysis is grounded in extensive field research conducted over five years across more than fifty cities in four countries. Thousands of archaeological artifacts—particularly Islamic tombstones and epigraphic inscriptions dating from the fourteenth to the sixteenth centuries—are examined and treated as primary legal-historical sources. The findings demonstrate that Islamic law had already operated as an autonomous, authoritative, and socially institutionalized legal system in the Nusantara well before the advent of European colonial rule. These empirical data directly challenge the foundational assumption of the Receptie Theory, which posits that Islamic law applied only to the extent that it was accepted by customary law. Instead, the evidence reveals a complex legal order in which Islamic norms functioned as positive law within political, social, and judicial structures. This study makes an academic contribution by deconstructing a long-standing colonial paradigm and reconstructing a more integrative historiography of Islamic law in the Nusantara. It advances postcolonial legal studies by offering an empirically grounded model for decolonizing Islamic legal historiography and re-centering indigenous Islamic legal agency in Southeast Asian history